2022
DOI: 10.1186/s13054-022-04192-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in participants with failure of initial antibacterial therapy for hospital-acquired/ventilator-associated bacterial pneumonia prior to enrollment in the randomized, controlled phase 3 ASPECT-NP trial of ceftolozane/tazobactam versus meropenem

Abstract: Background Ceftolozane/tazobactam, a combination antibacterial agent comprising an anti-pseudomonal cephalosporin and β-lactamase inhibitor, is approved for the treatment of hospital-acquired/ventilator-associated bacterial pneumonia (HABP/VABP) in adults. Participants in the ASPECT-NP trial received ceftolozane/tazobactam (3 g [2 g ceftolozane/1 g tazobactam] every 8 h) or meropenem (1 g every 8 h). Participants failing prior antibacterial therapy for the current HABP/VABP episode at study ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the subgroup of vHAP, the ASPECT-NP trial also demonstrated lower mortality in the arm of patients treated with TOL-TZB compared with the arm of patients treated with MEM [172]. This result was further evaluated with multivariable analysis by Kollef et al, confirming the protective effect of TOL-TZB in this special subgroup population [173], although additional studies are needed for confirmation of these findings.…”
Section: New Treatment Optionsmentioning
confidence: 79%
“…In the subgroup of vHAP, the ASPECT-NP trial also demonstrated lower mortality in the arm of patients treated with TOL-TZB compared with the arm of patients treated with MEM [172]. This result was further evaluated with multivariable analysis by Kollef et al, confirming the protective effect of TOL-TZB in this special subgroup population [173], although additional studies are needed for confirmation of these findings.…”
Section: New Treatment Optionsmentioning
confidence: 79%
“…2,3032,4648 Based on several randomized clinical trials conducted in recent years, Ceftolozane/Tazobactam has been found to be comparable to meropenem as an effective and safe treatment option for complicated and life-threatening infections caused by ESBL-producing Enterobacterales. 4955 Ceftolozane/Tazobactam may confer a survival advantage over meropenem in invasive ESBLs-related infections, leading to lower mortality. 52,54 However, this effect needs confirmation through adequately powered prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…4955 Ceftolozane/Tazobactam may confer a survival advantage over meropenem in invasive ESBLs-related infections, leading to lower mortality. 52,54 However, this effect needs confirmation through adequately powered prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Participants whose prior antibacterial therapy had failed for the current episode of pneumonia at study entry had lower 28-day all-cause mortality rates with ceftolozane/tazobactam versus meropenem treatment in the ASPECT-NP trial (22.6% [n = 12/53] vs 45.0% [n = 18/40], respectively) [ 61 ]. To examine this outcome in more detail, a post hoc analysis examining this important pre-defined patient population was conducted [ 61 ].…”
Section: Clinical Studies In Patients Treated With Ceftolozane/tazoba...mentioning
confidence: 99%
“…Participants whose prior antibacterial therapy had failed for the current episode of pneumonia at study entry had lower 28-day all-cause mortality rates with ceftolozane/tazobactam versus meropenem treatment in the ASPECT-NP trial (22.6% [n = 12/53] vs 45.0% [n = 18/40], respectively) [ 61 ]. To examine this outcome in more detail, a post hoc analysis examining this important pre-defined patient population was conducted [ 61 ]. Multivariable regression analysis determined that, after controlling for other factors, the risk of dying after treatment with ceftolozane/tazobactam was approximately one-quarter of that following treatment with meropenem (28-day all-cause mortality; odds ratio [OR] 0.23; 95% CI, 0.08–0.68), further supporting the use of ceftolozane/tazobactam in this patient population [ 61 ].…”
Section: Clinical Studies In Patients Treated With Ceftolozane/tazoba...mentioning
confidence: 99%